Rhizobacteria and Trichodermas antagonistic to the control of phytoparasitic nematodes in Barraganete plantain (Musa paradisiaca L. - Castillo Castillo, Alexander (2025)
El Carmen is considered the world capital of barraganete plantain (Musa paradisiaca L.) production. However, the lack of research limits the development of this crop. This study evaluated the effect of the synergistic application of Trichoderma spp. and plant growth-promoting rhizobacteria as biocontrol strategies against phytopathogenic nematodes. The aim was to improve crop yield and the control and reduction of this pathogen. The experiment was carried out under a completely randomized design (CRD) with five treatments and four replications, measuring growth and root characterization variables. The results showed a foliar emission of 3.42 leaves/month and a population density of Radopholus similis of 1,105 individuals. Plants treated with Trichoderma spp. and rhizobacteria showed a significant increase in the number of healthy roots (15.96) and the percentage of functional roots (58.49 %). Furthermore, rhizobacteria treatment increased pseudostem diameter to 1.75 cm and plant height to 36.31 cm. The chemical treatment yielded the highest root weight (147.7 g), while the control treatment showed the most damaged roots (13.29 g) and the lowest percentage of functional roots (49.44 g). These findings highlight the potential of using Trichoderma spp. in combination with rhizobacteria as an effective alternative for nematode biocontrol and strengthening plantain cultivation in El Carmen.